Qawāʿid al-Tafsīr sebagai Kerangka Epistemologis untuk Interpretasi Al-Qur’an yang Sah: Sebuah Studi Perbandingan Marāh Labīd dan al-Miṣbāḥ - Rokhim, Abdur; Fuad, Sahlul; Sahin, Cemal (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
The growing circulation of ideologically driven and methodologycally inconsistent Qur’anic interpretations highlights the absence of a clear epistemological standard for assessing interpretive validity. This study addresses this gap by examining Qawāʿid al‑Tafsīr as a structured epistemological model capable of guiding reliable Qur’anic interpretation. Using qualitative data derived from primary tafsīr texts, the study employyed a comparative hermeneutical method and critical textual analysis to evaluate two influential works in the Nusantara tradition: the nineteenth century Marāh Labīd by Shaykh Nawawi al‑Bantani and the contemporary Tafsīr al‑Miṣbāḥ by M. Quraish Shihab. The analysis is organized around five epistemological pillars that function as analytical domains, namely exegetical competence, ethical integrity, textual understanding, socio cultural contextual awareness and methodological coherence. The findings show three key patterns. First, both exegetes consistently apply these principles, demonstrating their normative relevance across historical contexts. Second, Nawawi al‑Bantani emphasizes textual stability and doctrinal continuity through classical linguistic analysis and transmitted readings. Third, Shihab prioritizes contextual relevance by employing thematic coherence and maqāṣid oriented reasoning. These differences illustrate the adaptability of Qawāʿid al‑Tafsīr to diverse interpretive orientations. The study concludes that Qawāʿid al‑Tafsīr provides a dynamic and universal framework for safeguarding interpretive validity. Its application strengthens Qur’anic hermeneutics in pluralistic societies and offers a practical tool for mitigating deviant interpretations while promoting responsible exegetical practice.